Islamic Human Resource Management dalam Pengembangan Profesionalisme Guru PAI: Integrasi Nilai Amanah, Ihsan, dan Kompetensi Profesional - Mutiara Sofa; Imron I (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of the professionalism of Islamic Religious Education (IRE) teachers requires not only the enhancement of professional competence but also the strengthening of Islamic spiritual values and work ethics. However, studies on the integration of the values of amanah (trustworthiness) and ihsan (excellence) within the framework of Islamic Human Resource Management (IHRM) for developing IRE teachers’ professionalism remain limited. This study aims to analyze the concept of Islamic Human Resource Management in enhancing the professionalism of Islamic Religious Education teachers through the integration of amanah, ihsan, and professional competence. This study employed a qualitative approach using library research. Data were collected through documentation studies from scientific articles, books, and relevant literature, and analyzed using content analysis techniques. The findings indicate that the implementation of IHRM in the development of IRE teachers can be carried out through recruitment, competency development, performance appraisal, and career development based on the values of amanah and ihsan. The value of amanah strengthens integrity, responsibility, and professional commitment, while ihsan encourages work quality, excellence, and continuous improvement. The novelty of this study lies in the conceptual construction of integrating modern human resource management practices with Islamic values as a holistic approach to enhancing the professionalism of Islamic Religious Education teachers.